Fenomena Ritual Mandi 7 Sumur Keramat di Vihara Gayatri, Cilangkap, Depok, Jawa Barat - Ryan Alviano; Madiyono Madiyono; Nyoto Nyoto (Jurnal Pelita Dharma, 2022)
Cleansing ritual of bathing at the 7 Gayatri Vihara Wells wasperformes not only by Buddhists but also by communities of diverse culturalbackground. It is known that most who perform the cleansing ritual areBuddhist. This fact it is interesting to research in the meaning of the 7 SacredWell in the society especially buddhist who perform cleansing ritual. Purposeof this research is to know the meaning of the 7 Sacred Well in The GayatriVihara, Cilangkap, Depok, West Java.The research uses qualitative approach with phenomenon model.Informant in this research are the owners, the believer, and the visitor of 7Sacred Well at the Gayatri Vihara. Data collecting technique used isobservation, interview, and documentation. Data analyzed using Miles,Huberman, and Saldana. Data validity technique are done with credibilitytest, transferability, dependability, and confirmability.The research concluded (1) the process concist of the ritual at 7 Wellsincludes cleansing the body with seven dipper at each wells, going to amerta’spools, plunging eight times, then cleansing the body of eight dipper at themiddle well, one dipper was taken to rinse (something); three times; prostrateat the well, toss a coin, follow instruction for cleansing; pray according tointention and believe; pray first before cleansing; cleansing first then prays.The purpose of the visitor are to prays and perform cleansing ritual,recreation, and asking help in resolving mortal problem. The expectation ofvisitors to perform the cleansing ritual is to gain health, trouble-freeingprosperity, get married, be reassure and hopeless. The cleansing ritual wasalso performed on kliwon Tuesday night, kliwon Friday, first suro night,bakcang days, a light moon night, and a dark moon night. Where at nightcleansing there is keyholder who helps the cleansing ritual and there is aceremony that become socialating between believer, visitors, and community;(2) visitors take to mean the ritual to outward and inner cleansing, reliefer,trust and believe, and just to be clean. Then the visitors view of the ritualphenomena at 7 Wells Gayatri Vihara if it believes it is can get beneficial thewells, there is for good, and purification and cleansing; (3) impact in spiritualsense are nothing (only an object of hope) and serene and sincere in the courseof life’s sorrows. Later on the life lessons gained form cleansing ritual for visitors are they have no lessons, and easy to concentrate, and more ease tofacing with life’s problems.